2009
DOI: 10.1002/lary.20762
|View full text |Cite
|
Sign up to set email alerts
|

Impact of thyroidectomy without laryngeal nerve injury on vocal quality characteristics: An objective multiparameter approach

Abstract: After thyroidectomy subjects had a normal perceptual and objective vocal quality corresponding with a Dysphonia Severity Index of 66%, and there is no permanent change of the vocal performance. Moreover, there is no psychosocial handicapping effect of the vocal quality, but immediately post-thyroidectomy there are more vocal complaints. To what extent thyroidectomy causes (temporary or permanent) alterations of the singing voice in elite vocal performers is subject to further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 25 publications
5
47
1
Order By: Relevance
“…In addition, perceptual analysis by a trained Speech Language Pathologist using the GRBAS scoring system did not reveal significant abnormalities in voice quality, despite patient perceptions of dysfunction. This is in agreement with the results from several studies where jitter, shimmer, MPT, ST range, and GRBAS measures were all within the normal range; often despite patient complaints of voice abnormalities [5,6,16,17]. In addition, studies have shown that 14-75% of patients continue to complain of voice symptoms 3 months −1 year post thyroidectomy, questioning the origin of these symptoms with regards to thyroid disease [4][5][6]16].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In addition, perceptual analysis by a trained Speech Language Pathologist using the GRBAS scoring system did not reveal significant abnormalities in voice quality, despite patient perceptions of dysfunction. This is in agreement with the results from several studies where jitter, shimmer, MPT, ST range, and GRBAS measures were all within the normal range; often despite patient complaints of voice abnormalities [5,6,16,17]. In addition, studies have shown that 14-75% of patients continue to complain of voice symptoms 3 months −1 year post thyroidectomy, questioning the origin of these symptoms with regards to thyroid disease [4][5][6]16].…”
Section: Discussionsupporting
confidence: 91%
“…A literature review found that the reported prevalence of compressive symptoms in pre-operative thyroidectomy patients varied widely between studies, ranging from 11-88% [1][2][3][4][5][6][7]. Unfortunately many of these studies vary with regards to the symptoms reported as well as the methods used for data collection (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, it is well known among thyroid surgeons that after thyroidectomy, most patients complain of some degree of mainly transient voice changes, even in the absence of laryngeal nerve injuries-postthyroidectomy syndrome. Voice changes after uncomplicated thyroidectomy have been assessed previously [5,8,10,16]. In the past, voice outcomes have relied upon perceptual judgement of voice quality and acoustic measurement of a periodicity in the speech signal.…”
Section: Discussionmentioning
confidence: 99%